EDUKASI MENGATASI PERMASALAHAN STUNTING DAN PENGOLAHAN BAHAN PANGAN LOKAL MENJADI MAKANAN YANG TINGGI PROTEIN DAN ZAT BESI BAGI MASYARAKAT DI KELURAHAN CEMANI SUKOHARJO - Ovikariani; Murtisiwi, Lusia; Putra, Greggy Giovananda Afandty; Agustin, Riska Sulistyani; Nani, Sisilia Laurentin Evelin; Sailirrahma, Nabila Sepgialuni (LPPM Universitas Awal Bros, 2025)
Stunting is a health problem that has an impact on inhibiting physical, mental, and health growth of children. Data obtained from the Central Statistics Agency of Sukoharjo District in 2023, the prevalence of stunting in the Sukoharjo area reached 24.3%. The Cemani area is included in one of the sub-districts in the Sukoharjo area. When viewed from the description of the problem, it is necessary to handle it through a community service program that aims to improve community understanding and skills in processing local fish into healthy food as an effort to prevent stunting. Community service activities were carried out at the Nusa Idah Posyandu Center, Cemani, which consisted of several stages such as planning, implementation, pre-test, socialization, product demonstration, Q&A and post-test. The results of the community service activities were that the activities ran smoothly with 37 participants attending. The question and answer session showed that participants were interested in the demonstration of the use of local food ingredients as a solution to prevent stunting. In addition, the community service carried out was able to increase community understanding as evidenced by the average pre-test score of 71.25 to a post-test score of 81.76. Based on the description, it can be concluded that the community service program carried out was successful in increasing the understanding and skills of the community in Cemani Village.